Magnesium deficiency induced leaf chlorosis affects plant growth, mineral concentration and fruit quality in field pomelo trees - Jiuxin Guo; Xiaona Li; Yuwen Wang; Wenlang Hu; Lijun Zhang; Ziwei Luo; Hao Xu; Li-Song Chen (Journal of Agriculture and Food Research)
Healthy trees are considered the foundation for high-quality pomelo production; however, leaf chlorosis frequently happens in pomelo orchards, and the reasons and adverse effects on plant growth and fruit quality are poorly understood. We conducted a field investigation with six paired groups between the yellow and green leaves of pomelo trees to analyze the growth, mineral and quality characteristics in different leaf positions and fruit parts. Compared with green pomelo trees, the concentrations of nitrogen (N), phosphorus (P), calcium (Ca), and magnesium (Mg) were decreased and increased potassium (K) in various leaf organs of yellow pomelo trees, resulting in accumulated non-structural carbohydrates and reduced growth variables (including SPAD value as relative chlorophyll content, dry weight, leaf area, water content, and specific leaf weight), which was amplified with fruit than without fruit. Also, there was the highest positive correlation between leaf Mg concentration and SPAD value, further confirmed by the path analysis and random forest analysis, implying that Mg is the main factor affecting leaf chlorosis. Moreover, leaf chlorosis also affected fruit quality, in which the concentrations of N, P and Ca were decreased and increased K and Mg, with lower sugar content (including total soluble sugar, sucrose, and total soluble solids) and higher acidity content (including pH, vitamin C, and titratable acidity), resulting in decreased total soluble solids/titratable acidity and antioxidant capacity (less phenol content). The positive correlations between leaf Mg concentration and fruit quality parameters were also observed. However, these measured parameters were highly separated and accounted for 53.1 % of leaf and fruit organs between the yellow and green leaves of pomelo trees. Overall, our results demonstrate that Mg deficiency induced leaf chlorosis affects plant growth and fruit quality in pomelo trees, that SPAD can be used to monitor leaf Mg status, and these findings provide the basis for optimized nutrient management in sustainable pomelo production.